A review on microstructural study and compressive strength of geopolymer mortar, paste and concrete - Ng C.; Alengaram U.J.; Wong L.S.; Mo K.H.; Jumaat M.Z.; Ramesh S. (Elsevier Ltd, 2023)
Aluminosilicates; Binders; Compressive strength; Computerized tomography; Concretes; Curing; Inorganic polymers; Microcracking; Microcracks; Microstructure; Mortar; Portland cement; Sodium hydroxide; Alkali activators; Cementitious properties; Geopolymer; Industrial by-products; Microstructural investigation; Microstructure analysis; Ordinary Portland cement; Sodium hydroxide solutions; Geopolymers